2022
DOI: 10.1162/opmi_a_00064
|View full text |Cite
|
Sign up to set email alerts
|

Simplification Is Not Dominant in the Evolution of Chinese Characters

Abstract: Linguistic systems are hypothesised to be shaped by pressures towards communicative efficiency that drive processes of simplification. A longstanding illustration of this idea is the claim that Chinese characters have progressively simplified over time. Here we test this claim by analyzing a dataset with more than a million images of Chinese characters spanning more than 3,000 years of recorded history. We find no consistent evidence of simplification through time, and contrary to popular belief we find that m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…For example, if one character has a PC score of 19.8 while another has a score of 20.1, rounding these scores will make their complexity equivalent even though they are not exactly equivalent. Second, both complexity scores seem to be highly correlated, with a Pearson correlation of r = .80 (Koshevoy et al, 2023), which mirrors previous comparisons of complexity measures for Chinese (Han et al, 2022). Therefore, we found this to be redundant and not necessary for our purposes.…”
Section: Perimetric Complexitysupporting
confidence: 82%
See 3 more Smart Citations
“…For example, if one character has a PC score of 19.8 while another has a score of 20.1, rounding these scores will make their complexity equivalent even though they are not exactly equivalent. Second, both complexity scores seem to be highly correlated, with a Pearson correlation of r = .80 (Koshevoy et al, 2023), which mirrors previous comparisons of complexity measures for Chinese (Han et al, 2022). Therefore, we found this to be redundant and not necessary for our purposes.…”
Section: Perimetric Complexitysupporting
confidence: 82%
“…Another study looked at the relationship between frequency and complexity across characters in five scripts in Chinese history (oracle bone, bronze, small seal, traditional, and simplified scripts; Han et al, 2022). It was shown that frequency had a consistently negative but curvilinear association with complexity.…”
Section: The Principle Of Least Complexitymentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, a more accurate wording, which is adequate for describing the time evolution of alphabets, is "compression" and not "simplification" [10]. This idea was exemplified recently by analysis of Chinese characters spanning more than 3000 years of recorded history [12]. No consistent evidence of simplification through time was revealed [11].…”
Section: Introductionmentioning
confidence: 99%